m6A Modifications Play Crucial Roles in Glial Cell Development and Brain Tumorigenesis - Wang, Jing; Sha, Yongqiang; Sun, Tao (Frontiers in Oncology, 2021)
RNA methylation is a reversible post-transcriptional modification to RNA and has a significant impact on numerous biological processes. N6-methyladenosine (m6A) is known as one of the most common types of eukaryotic mRNA methylation modifications, and exists in a wide variety of organisms, including viruses, yeast, plants, mice and humans. Widespread and dynamic m6A methylation is identified in distinct developmental stages in the brain, and controls development of neural stem cells and their differentiation into neurons, glial cells such as oligodendrocytes and astrocytes. Here we summarize recent advances in our understanding of RNA methylation regulation in gliogenesis and its dysregulation in brain tumors. This review will highlight biological functions of RNA methylation in development of oligodendrocytes and astrocytes, and provide insights into brain tumor formation, and diagnostic and treatment strategies.